Contextualization of the Hudud Verse in Tafsir An-Nur: The Maqasid Asy-Syari’ah Approach in Indonesia - M. Nabih Z. A. Nabih; Leni Nur Azizah Leni; Nor Ichwan Ichwan (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2025)
The hudud verses in the Qur’an, such as the prescribed punishment in Islamic law for theft, which includes hand amputation, are often the subject of debate regarding their application in the modern legal system, especially in Indonesia. As a country with a majority Muslim population, Indonesia is faced with a significant challenge to balance the application of sharia with a national legal system influenced by Western laws and local customs. This study analyzes Hasbi Ash-Shiddiqiey's interpretation of the hudud verse in Tafsir An-Nur. This study examines how Hasbi contextualizes the application of hudud law by considering maqasid asy-syari’ah, as well as Indonesia's complex and diverse socio-legal conditions. The method used in this study is a qualitative approach with an in-depth analysis of the text of Tafsir An-Nur through the framework of maqasid asy-syari’ah. The study results revealed that Hasbi was not fixated on literal interpretation, but rather considered social factors, such as poverty and social justice, in the application of hudud. The contextual approach emphasizes the importance of protecting fundamental rights and people's welfare, thus making Tafsir An-Nur relevant in Indonesia's pluralistic legal system.